2015
DOI: 10.1038/ncomms9114
|View full text |Cite
|
Sign up to set email alerts
|

V1 neurons respond differently to object motion versus motion from eye movements

Abstract: How does the visual system differentiate self-generated motion from motion in the external world? Humans can discern object motion from identical retinal image displacements induced by eye movements, but the brain mechanisms underlying this ability are unknown. Here we exploit the frequent production of microsaccades during ocular fixation in the primate to compare primary visual cortical responses to self-generated motion (real microsaccades) versus motion in the external world (object motion mimicking micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 52 publications
8
48
0
Order By: Relevance
“…Iig andThier, 1996, Fischer et al, 1981). Others have reported responses that were mostly compatible with at least some level of extra-retinal modulation (e.g., Gawne andMartin, 2002, Kagan et al, 2008) and some have argued strongly for differential responses, including very recent work readdressing this old but yet unsettled question (Troncoso et al, 2015, e.g., McFarland et al, 2015. This discrepancy across studies may be related to differences in the experimental paradigms and data analysis methods employed (Troncoso et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Iig andThier, 1996, Fischer et al, 1981). Others have reported responses that were mostly compatible with at least some level of extra-retinal modulation (e.g., Gawne andMartin, 2002, Kagan et al, 2008) and some have argued strongly for differential responses, including very recent work readdressing this old but yet unsettled question (Troncoso et al, 2015, e.g., McFarland et al, 2015. This discrepancy across studies may be related to differences in the experimental paradigms and data analysis methods employed (Troncoso et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These analyses revealed that the prevalence of microsaccades transiently rose before periods of increased visibility, and transiently dropped before periods of diminished visibility for all SFs tested. In combination with our previous recordings of microsaccade‐triggered neural transients in the primate visual system (Martinez‐Conde et al ., , ; Troncoso et al ., ), the present results support the proposal that transients from microsaccades are beneficial to perception (Livingstone et al ., ; Macknik & Livingstone, ; Martinez‐Conde et al ., , ). More generally, our findings suggest that microsaccades do not modulate perception in exceptional circumstances applying only to narrow stimuli sets or viewing conditions, but as a habitual rule.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have also implicated the rebound response in the issue of saccade-based termination (Niemeyer and Paradiso 2018) and object motion versus motion from eye movements (Troncoso et al 2015). In addition, the rebound response can be used by the visual system as a tool for memory storage and, thus, to overcome the tendency of certain neurons to signal a transient response and, therefore, to transmit only or mainly, changes in time.…”
Section: Previous Computational Models -mentioning
confidence: 99%